Tingkat Kesehatan Bank Berdasarkan Analisis RGEC Pada Bank BNI 46 - Pupu Sopini (Ekonomis: Journal of Economics and Business, 2018)
This research aims to know the level of health of Bank BNI 46 using RGEC (Risk Profile, Good Corporate Governance, Earning, Capital). Assessment of the health of the bank rate is used to determine whether the bank is in a very healthy condition, healthy, reasonably healthy, less healthy, or unhealthy. A healthy bank is a bank that is able to keep and maintain the trust of the community, can perform the function of intermediary, can help smooth the payment traffic and can be used by the Government in implementing the various policies relating to, especially monetary policy. This type of research uses descriptive analysis methods with quantitative approach that aims to describe systematically and factual about the facts as well as the relationships between variables are investigated by means of collecting data, processing menginterprestasikan, analyze, and secondary data from the financial statements of Bank BNI 46. The results showed that the Risk profiles of the components of the Non Performing Loan (NPL) average value below 2% which means that bank BNI 46 are at a very healthy state, means the bank can control the risk of going bad credit happens. As for the components of the Loan to Deposit Ratio (LDR) bank BNI 46 from 2012-2016 experience fluctuating growth declines and are in the position well enough. This suggests that the ability of the lower liquidity of bank BNI 46. The results of the rating component of Good Corporate Governance (GCG) is at rank 2 which means in a State of healthy, so the bank has good corporate governance. Assessment of Earnings/earning ratios seen from the value of the Return on Equity (ROE) above 15% very good circumstances, it means that the bank maintains consistent gains its profits. NET Interest Margin (NIM)) bank BNI 46 in 2007-2016 have a rating above 3% NIM means the bank is in very good condition.  Value-based capital components Capital Adequacy Ratio (CAR) have a rating above 11% which means it is in very good condition. This means bank BNI 46 have capital adequacy to fulfill obligations that are owned, both in its business activities as well as funding to cover the risk in the future.